Comparative efficacy of surgery and radiotherapy in achieving local control in Kimura disease: a retrospective analysis of treatment outcomes - Lv, Wenlong; Chen, Yanbin; Wang, Xuezhen; Li, Shan; Liu, Feng; Hong, Jinsheng (Frontiers in Oncology, 2025)
ObjectiveTo evaluate and compare the impact of surgery versus radiotherapy on local control rates in Kimura disease (KD).MethodsA retrospective analysis was conducted on 26 patients diagnosed with KD at the First Affiliated Hospital of Fujian Medical University from January 2001 to January 2024. Patients were categorized into four treatment groups: Primary Surgery (PS), Primary Radiotherapy (PR), Salvage Surgery (SS), and Salvage Radiotherapy (SR) following recurrence. Data on demographics, tumor characteristics, eosinophil counts (EO), disease duration, and radiation dose were collected. Univariate and multivariate analyses were performed to identify factors influencing local control rates.ResultsThe cohort had a mean age of 42.2 ± 17.7 years, with 24 male patients. Kaplan-Meier analysis revealed that radiotherapy provided superior local control compared to surgery, with significant differences between PS and PR (p = 0.047) and SS and SR (p < 0.001). No significant difference was found between PR and SR (p = 0.816). Multivariate analysis identified treatment modality as the strongest predictor of recurrence (HR: 0.062). Additionally, factors such as radiotherapy, bilateral involvement, and longer disease duration were associated with improved local control. Among radiotherapy patients, age, tumor number, tumor size, pre-treatment eosinophil count, radiotherapy dose, and disease duration significantly influenced prognosis.ConclusionRadiotherapy is more effective than surgery in achieving local control of Kimura disease. Higher radiation doses may negatively impact outcomes, suggesting that a tailored, moderate-dose approach is optimal. Radiotherapy should be prioritized, particularly for recurrent or multifocal cases, offering a more reliable long-term treatment strategy than surgery.